Exploration of Mechanical Energy in the Pletokan Traditional Game as Ethnophysics Based Learning Media - Icha Fauzyah Rossiana; Habibi Habibi; Galuh Aryseno (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
The integration of local culture in science learning through an ethnophysics approach can create contextual and meaningful learning experiences. However, studies specifically exploring the concept of mechanical energy in traditional games are still limited. This study aims to explore the concept of mechanical energy in the traditional Pletokan game and analyze its potential as an ethnophysics-based physics learning medium. The novelty of this research lies in the exploration of potential energy, kinetic energy, and mechanical energy concepts in the Pletokan game from an ethnophysics perspective. This study used a descriptive qualitative approach with an exploratory design. Data were collected through observation, documentation, and literature studies related to the mechanism of the Pletokan game and the physical phenomena occurring during gameplay. The results showed that the Pletokan game contains concepts of potential energy, kinetic energy, mechanical energy, and energy transformation. These concepts appear during the process of air compression, projectile motion, and the emergence of the characteristic “pletok” sound. The findings indicate that the Pletokan game has the potential to be used as an ethnophysics-based physics learning medium that connects physics concepts with local culture in a contextual way. This study implies that traditional games can support innovative physics learning while preserving local cultural values.